2022
DOI: 10.1002/jpen.2406
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid model of compounded and multichamber bag parenteral nutrition for adults with chronic intestinal failure

Abstract: Background Although international guidelines support the use of commercially available multichamber bags (MCBs), the majority of home parenteral nutrition (HPN) in the United Kingdom has been compounded PN, tailored to the patient. However, national capacity limitations in aseptic facilities have necessitated the increased use of MCBs. There are no studies evaluating the appropriateness or benefits of using a “hybrid” regimen incorporating both MCBs and compounded PN in patients already established on compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…When the nitrogen, lipid and glucose content was compared in those with malignant indications for HPN, no difference was observed. 56 When types of HPN were compared, 47,48 standard and individually compound HPN prescriptions varied in nutrient content, although the reasons for this were not evaluated in terms of clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When the nitrogen, lipid and glucose content was compared in those with malignant indications for HPN, no difference was observed. 56 When types of HPN were compared, 47,48 standard and individually compound HPN prescriptions varied in nutrient content, although the reasons for this were not evaluated in terms of clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting HPN composition have indicated that electrolyte requirements differ based on the type of HPN type 47,48 and IF classification, 49,56 but further information is lacking on what drives requirements beyond typical amounts provided by standardised HPN admixtures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations